MANAJEMEN LABA: PERAN KEAKTIFAN KOMITE AUDIT DAN AUDITOR EKSTERNAL BIG FOUR (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2013-2015) - Suci Rahmadani; Haryanto Haryanto (Jurnal Akuntansi Aktual, 2018)
This study aims to determine: (1) the effect of activeness of the audit committee on earnings management, (2) the effect of external audit by Big Four on earnings management, (3) the effect of combination between activeness of the audit committee and external audit on earnings management. Audit committee and external audit have a very important role to oversee the financial reporting process and monitor the propensity of a company managers to manipulate earnings. Monitoring mechanism is a key factor to reduce conflict of interest and any opportunistic behavior from the manager. This study uses secondary data from annual reports and financial statements on manufacture companies listed on Indonesian Stock Exchange period 2013-2015 by using purposive sampling method. There are 67 companies samples or 201 observations that meet the criteria of the study sample. Analysis method in this research is Ordinary Least Square regression analysis. The results of this study indicate that the activeness of the audit committee indicate not significantly reduce earnings management. External audit by Big Four can decrease earnings management significantly. However, the combination activeness of the audit committee and external audit by Big Four indicate potential increase in earnings management significantly.